2019
DOI: 10.3390/su11174784
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lignocellulosic Waste Pre-Treatment on the Characteristics of Bond Rupture

Abstract: Post-harvest crop residues are an interesting raw material for the production of composite materials. However, their surface often contains waxy and siliceous substances, which can cause adhesion problems. Therefore, various surface pre-treatment methods have been developed to increase the surface tension of these particles and hence to improve adhesive adhesion. The influence of hydrothermal, chemical, plasma and enzymatic treatment was investigated. The aim of the paper is to evaluate the effect of pre-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the biochemical properties of ligno-cellulosic materials, as straw, make it suitable for further industrial processing. For instance, Fang and Shen [8] reported the suitability of straw for paper and paperboard production, Hýsek et al [9] highlighted the possibility to exploit cereal residues for composite material production, while Swain et al [10] investigated the hydrolyzation of cellulose and the hemicellulose of straw into fermentable sugars, which are particularly attractive for bioethanol production industries. Recently, it has been found that winter wheat straw can be returned to soil as biochar to enhance the yield in corn and peanut cultivation [11].…”
Section: Frameworkmentioning
confidence: 99%
“…However, the biochemical properties of ligno-cellulosic materials, as straw, make it suitable for further industrial processing. For instance, Fang and Shen [8] reported the suitability of straw for paper and paperboard production, Hýsek et al [9] highlighted the possibility to exploit cereal residues for composite material production, while Swain et al [10] investigated the hydrolyzation of cellulose and the hemicellulose of straw into fermentable sugars, which are particularly attractive for bioethanol production industries. Recently, it has been found that winter wheat straw can be returned to soil as biochar to enhance the yield in corn and peanut cultivation [11].…”
Section: Frameworkmentioning
confidence: 99%